Stowaway - Anderson, John David, 1975- (Anderson, John David, 1975- Icarus chronicles, 2022)
Caught up in an intergalactic war, twelve-year-old Leo and his family are living aboard a research vessel where his scientist father works after they escaped Earth, which is caught up in a war among two species of aliens vying for extraction of a new, valuable mineral found in the Earth's crust. Still reeling from his mother's death during the war, Leo experiences further tragedy when his father is captured and he must stow away on a pirate ship, hoping to gain the trust of a ragtag group of aliens looking out for themselves in order to get help for those left on board his father's ship.